A method for improving the accuracy of calibration-free laser-induced breakdown spectroscopy (CF-LIBS) using determined plasma temperature by genetic algorithm (GA). Issue 6 (27th June 2015) - Dong, Juan; Liang, Long; Wei, Jiao; Tang, Hongsheng; Zhang, Tianlong; Yang, Xiaofeng; Wang, Kang; Li, Hua
<x xml:space="preserve">Abstract</x> An internal reference-external standard with iteration correction (IRESIC) method is proposed to correct for the self-absorption effect and plasma temperature in CF-LIBS based on an internal reference line and one standard sample.